2017
DOI: 10.1002/jcsm.12206
|View full text |Cite
|
Sign up to set email alerts
|

Muscle mass and association to quality of life in non‐small cell lung cancer patients

Abstract: BackgroundCancer wasting is characterized by muscle loss and may contribute to fatigue and poor quality of life (QoL). Our aim was to investigate associations between skeletal muscle index (SMI) and skeletal muscle radiodensity (SMD) and selected QoL outcomes in advanced non‐small cell lung cancer (NSCLC) at diagnosis.MethodsBaseline data from patients with stage IIIB/IV NSCLC and performance status 0–2 enrolled in three randomized trials of first‐line chemotherapy (n = 1305) were analysed. Associations betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
137
3

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(153 citation statements)
references
References 48 publications
(92 reference statements)
6
137
3
Order By: Relevance
“…Moreover, we could not determine the relation between skeletal muscle features and quality of life, clinical outcomes, or muscle function or strength because these data were not prospectively collected in our study. In metastatic lung cancer patients treated with first‐line systemic therapy, clinical outcomes and global quality of life were positively associated with skeletal muscle features . This deserves further study in esophagogastric cancer patients.…”
Section: Discussionmentioning
confidence: 76%
“…Moreover, we could not determine the relation between skeletal muscle features and quality of life, clinical outcomes, or muscle function or strength because these data were not prospectively collected in our study. In metastatic lung cancer patients treated with first‐line systemic therapy, clinical outcomes and global quality of life were positively associated with skeletal muscle features . This deserves further study in esophagogastric cancer patients.…”
Section: Discussionmentioning
confidence: 76%
“…In recent years, studies in area of body composition and cancer have focused on the relationship between the quantity and quality of the skeletal muscle in outcomes such as mortality and quality of life . About toxicity outcome, previous studies have already shown the impact of sarcopenia for different gastrointestinal cancers such as colon and rectum, oesophagus, breast cancer, and gastric cancer .…”
Section: Discussionmentioning
confidence: 99%
“…In lung cancer, SMM waisting (sarcopenia) has been linked to shorter survival, reduced tolerance to chemotherapy, decreased QoL, and diminished functional ability . The importance of detecting sarcopenia has been stressed by many, and as obesity continues to increase, high body mass index (BMI) in patients diagnosed with cancer could lead clinicians to underestimate the extent of muscle loss.…”
Section: Introductionmentioning
confidence: 99%